Technical and legal standards for implementation: water and sewerage master plan for sixth class municipalities in eastern Cundinamarca (2015)
With this paper seeks to highlight the extent to which the project will implement the master of water and sewage in the municipalities of eastern Sixth category Cundinamarca plan. Municipalities that have had steady growth of population and for which it is very important to put developing this theme, since thereby the quality of life of the community were improved. Therefore technical and legal regulations in force for the project will be discussed. The water and sewerage master plan takes into account important issues: political, social, economic, geographical and environmental level so collect the necessary information from stakeholders and official sources as DANE or the municipal authorities for implementation plan, seeking to obtain desired results while minimizing negative impacts on the time the plan takes the implementation and meets the projection (long term). Opportunity to contribute works to improve the lives of all people residing in the urban area, using the financial resources which may be available for the common benefit guaranteeing a healthy environment.